World Investment and Political Risk 2009 - Multilateral Investment Guarantee Agency (World Bank, 2012)
Political risk is a top concern for corporate foreign investors from industrialized but also developing countries when venturing into emerging markets. At the same time, these investors maintain a positive outlook on economic and business prospects in the developing world, which is expected to attract a growing share of global foreign direct investment (FDI) as the world economy slowly, recovers. Positive business sentiment over emerging markets amid concerns over political perils point to a sustained need to mitigate these perils. This, added to the rise of South-based investors, offers opportunities and challenges for the political risk insurance (PRI) industry. In the current context of high uncertainty, understanding how investors perceive and deal with political risks helps to map out the role of PRI in the emerging post-crisis investment landscape. This report focuses on FDI and PRI for long-term investment, and only covers political risk in developing countries. Although political risk also affects other forms of private capital flows, these are beyond the scope of this publication. The main findings of the report are summarized as follows: i) while political risks top foreign investors' concerns, the global economic and financial crisis has not fundamentally altered FDI prospects for emerging markets; ii) concerns over political risks, combined with sustained FDI into emerging markets over the medium term, suggest a growing need for political risk mitigation and opportunities for the PRI industry; and iii) the emergence of South-based investors is increasingly shaping the global FDI environment and presents regional growth opportunities, but also challenges, for the PRI industry.